Studies on copper slag substitution for sand in high strength concrete - Palani, T.; Jaya, K.P.; Muthumani, K. (Journal of Structural Engineering, 2024)
This paper presents the study on High Strength Concrete (HSC) made of copper slag (CS) as replacement to natural sand. The results obtained ensure alternative use of copper slag for complete substitute of natural sand (fine aggregate). The strength characteristics were assessed at constant workability. Eleven different mixture proportions of copper slag by weight replacement of natural sand from 0% to 100% with 10% increment for three different grades of High Strength Concrete via M40, M60 and M80 were studied. In this study the strength characteristics such as compressive strength, split tensile strength, flexural strength and the durability characteristics such as permeability and water absorption were investigated. The investigation show that the strength characteristics such as compressive strength, tensile strength and flexural strength increase continuously and the durability indicators such as water absorption and permeability decrease continuously with increase in copper slag proportion, without loss of workability and no significant changes in the fresh concrete. The optimum proportion of copper slag is found to be 100% for all the strength and durability parameters for all three grades of concrete considered in this study (i.e. M40, M60 & M80), hence copper slag appears as the best alternate material to natural sand.